2021
DOI: 10.1111/eos.12800
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and morbidity of biodegradable versus titanium osteosyntheses in orthognathic surgery: A systematic review with meta‐analysis and trial sequential analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 83 publications
(329 reference statements)
2
22
0
Order By: Relevance
“…Within the limitations of finite element analyses (e.g., assuming the masticatory forces are fixed), three-dimensional analyses indicated that the biomechanical stresses surrounding osteosynthesis systems remain far below the threshold of their ultimate strength of both biodegradable and titanium osteosynthesis systems [ 163 , 172 , 182 , 183 ]. In addition, the empirical evidence of fracture [ 19 ] and osteotomy [ 184 ] osteosyntheses shows that the efficacy of titanium and biodegradable osteosyntheses is similar (e.g., absence of malunion), indicating that the less favorable mechanical properties of biodegradable osteosynthesis are still sufficient to achieve similar healing outcomes. However, as also observed from the empirical evidence, the mechanical properties of biodegradable osteosyntheses of mandibular osteotomies may be insufficient to avoid micromovements [ 184 ].…”
Section: Pre-clinical Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Within the limitations of finite element analyses (e.g., assuming the masticatory forces are fixed), three-dimensional analyses indicated that the biomechanical stresses surrounding osteosynthesis systems remain far below the threshold of their ultimate strength of both biodegradable and titanium osteosynthesis systems [ 163 , 172 , 182 , 183 ]. In addition, the empirical evidence of fracture [ 19 ] and osteotomy [ 184 ] osteosyntheses shows that the efficacy of titanium and biodegradable osteosyntheses is similar (e.g., absence of malunion), indicating that the less favorable mechanical properties of biodegradable osteosynthesis are still sufficient to achieve similar healing outcomes. However, as also observed from the empirical evidence, the mechanical properties of biodegradable osteosyntheses of mandibular osteotomies may be insufficient to avoid micromovements [ 184 ].…”
Section: Pre-clinical Evidencementioning
confidence: 99%
“…In addition, the empirical evidence of fracture [ 19 ] and osteotomy [ 184 ] osteosyntheses shows that the efficacy of titanium and biodegradable osteosyntheses is similar (e.g., absence of malunion), indicating that the less favorable mechanical properties of biodegradable osteosynthesis are still sufficient to achieve similar healing outcomes. However, as also observed from the empirical evidence, the mechanical properties of biodegradable osteosyntheses of mandibular osteotomies may be insufficient to avoid micromovements [ 184 ]. Future research should also focus on these micromovements since they play an important role in developing foreign body reactions [ 26 ].…”
Section: Pre-clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Currently, titanium osteosynthesis systems are considered the gold standard to fixate bone segments in oral and maxillofacial surgery (OMF-surgery) [ 7 , 8 ], and orthopedics and trauma surgery [ 9 ]. However, the disadvantages of titanium systems include temperature sensitivity [ 10 ], tactile sensations of the plates and screws [ 11 ], growth restrictions [ 12 ], hampering of imaging and radiotherapy [ [13] , [14] , [15] ], presence of titanium particles in lymph nodes [ 16 ], extreme stiffness causing stress shielding of the underlying bone [ 2 ] and increased risk of medication-related osteonecrosis of the jaws [ 6 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The removal rate of polymeric biodegradable osteosynthesis systems in OMF-surgery is less and the disadvantages of titanium osteosyntheses are avoided [ 7 , 8 ]. Biodegradable systems should, preferably, be completely resorbed after 3–12 months [ 6 ].…”
Section: Introductionmentioning
confidence: 99%